Seroprevalence of human fascioliasis in Van province, Turkey - Taş Cengiz, Zeynep; Yılmaz, Hasan; Dülger, Ahmet Cumhur; Akdeniz, Hayrettin; Karahocagil, Mustafa Kasım; Çiçek, Mutalip (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Fasciola hepatica is a rare zoonotic parasite that infects the liver of many mammals including humans. The aim of this study was to determine the seroprevalence of fascioliasis in Van province by ELISA (antibody detection) on the assumption that not all cases could be detected by stool examination alone. Materials and Methods: A total of randomly selected 1,600 patients, directed from affiliated outpatient clinics to Yüzüncü Yıl University Medical Faculty Parasitology Laboratory, were enrolled in the study. Their mean age was 44.44±19.00 years. Blood samples were collected from all the patients, and their stool samples were examined. For the stool examination, native-lugol and sedimentation (in formalin-ethyl acetate) methods were employed. ELISA for F. hepatica was performed on the blood samples from all patients. Seropositive patients were treated with triclabendazole. Results: F. hepatica was detected by ELISA in 89 (5.6%) of the 1,600 patients, but eggs were identified on the stool examination in only 29 (1.8%) patients. The prevalence of F. hepatica was higher in females (7.2%) than in males (4.2%) and was higher in the ≥36-year age group (6.7%) than in the ≤35-year age group (4.4%). Abdominal pain (93.3%), fatigue (88.8%), and weight loss (69.7%) were the most common symptoms. Eosinophilia was present in 89.9% of the patients. All seropositive patients had a history of eating raw aquatic plants. Conclusion: Stool examination alone is not sufficient to diagnose F. hepatica. Serological tests such as ELISA must be used together with stool examination.